2023
DOI: 10.1002/smll.202304033
|View full text |Cite
|
Sign up to set email alerts
|

High Sensitivity, Wide Linear‐Range Strain Sensor Based on MXene/AgNW Composite Film with Hierarchical Microcrack

Ting Wang,
Zhiguang Qiu,
Haichuan Li
et al.

Abstract: Stretchable strain sensors suffer the trade‐off between sensitivity and linear sensing range. Developing sensors with both high sensitivity and wide linear range remains a formidable challenge. Different from conventional methods that rely on the structure design of sensing nanomaterial or substrate, here a heterogeneous‐surface strategy for silver nanowires (AgNWs) and MXene is proposed to construct a hierarchical microcrack (HMC) strain sensor. The heterogeneous surface with distinct differences in cracks an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 62 publications
(79 reference statements)
0
10
0
Order By: Relevance
“…The second form of nanocomposite to be analysed are layer deposition or coated nanocomposites. For these materials, nanosheet colloidal suspensions are drop-cast [176][177][178][179][180][181][182][183][184], dip-coated [185][186][187][188][189][190][191][192][193][194][195][196], spread coated [197], spray coated [198][199][200][201], spin coated [202] or screen printed [203][204][205][206] onto a flexible substrate or scaffold. Generally, the substrates are heated during these processes to facilitate solvent evaporation and allow for thin percolative networks of nanosheets to evenly form.…”
Section: Cyclic Signal Decaymentioning
confidence: 99%
“…The second form of nanocomposite to be analysed are layer deposition or coated nanocomposites. For these materials, nanosheet colloidal suspensions are drop-cast [176][177][178][179][180][181][182][183][184], dip-coated [185][186][187][188][189][190][191][192][193][194][195][196], spread coated [197], spray coated [198][199][200][201], spin coated [202] or screen printed [203][204][205][206] onto a flexible substrate or scaffold. Generally, the substrates are heated during these processes to facilitate solvent evaporation and allow for thin percolative networks of nanosheets to evenly form.…”
Section: Cyclic Signal Decaymentioning
confidence: 99%
“…Stretchable strain sensors based on bulk elastic composites composed of elastomers and nanoconductors have either relatively high yet fluctuant strain sensitivity or relatively stable but low sensitivity for a narrow strain range with piecewise resistance-strain signal linearity. To alleviate the contradiction between strain sensitivity and stretchability, the microcrack strategy was proposed for bilayer film strain sensors composed of elastomer films and electrically conductive nanomaterials to achieve both high strain sensitivity and stretchability. , However, abrupt generation of cut-through microcracks in rigid conductive materials is usually unpredictable and uncontrollable when subjected to tensile strain induced by elastic substrate deformation, owing to the large elasticity mismatch between elastomers and conductive networks. As the release of highly concentrated strain energy at the microcrack tip of homogeneous materials tends to generate cut-through cracks in electrically conductive paths on the film surface at low strain, it leads to low signal-to-noise ratio and poor reproducibility, as well as a narrow strain range. ,, As a remedy, the conductive layer composed by zero-dimensional nanoparticles is conducive to generating lots of microcracks due to the easy loss of contacts between nanoparticles upon strain, , which is capable of optimizing the signal-to-noise ratio to some extent.…”
Section: Introductionmentioning
confidence: 99%
“…To date, MXene-based strain sensors and actuators have been widely investigated. For instance, Wang et al 22 reported a strain sensor based on MXene-/silver-nanowire (AgNW)composite with hierarchical cracks, realizing high sensitivity and a wide linear range. Yang et al 25 fabricated an ultrasensitive, multidirectional flexible strain sensor with periodic wrinkles by transferring an MXene film onto a prestretched PDMS substrate and then releasing the prestrain.…”
Section: Introductionmentioning
confidence: 99%
“…MXene, as a new type of two-dimensional material, shows great potential for preparing various devices (e.g., sensors, actuators, and energy storage devices , ) due to its excellent mechanical flexibility, good electrical conductivity, hydrophilicity, and high photothermal conversion efficiency. To date, MXene-based strain sensors and actuators have been widely investigated.…”
Section: Introductionmentioning
confidence: 99%